Analisa Stabilitas Lereng pada Ruas Jalan Patung Lembuswana – Sebulu Sta 31+975 Provinsi Kalimantan Timur - Amir, Amir; Munajir, Achmad; Wijaya, Hendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The construction of the Patung Lembuswana–Sebulu STA 31+975 road section in East Kalimantan faces slope stability challenges due to hilly topography and high rainfall, which trigger landslides. This study aims to analyze slope stability using the Fellenius method, evaluate the safety of retaining walls with Rankine and Coulomb approaches, and design pile foundations based on site geotechnical data. The analysis shows a slope safety factor value of less than 1.5, indicating instability. The retaining wall is safe against overturning (safety factor > 2), but unsafe against sliding and bearing capacity failure. The pile foundation design provides a bearing capacity of 823.593 tons, exceeding the planned load of 482.743 tons, and is therefore considered safe. A combination of slope reinforcement, retaining wall design, and pile foundations is recommended to improve overall stability and reduce landslide risk at the project sit.